The Effectiveness of Scenario-Based Simulation Training for Perianesthetic Emergencies on Anesthesia Nurses’ Preparedness and Accuracy of Clinical Interventions - Dewi Kartika Sari; Aric Frendy Andriyan; Elisa Ayudia; Binuri Nisya Fi Amanillah (Indonesian Journal of Global Health Research, 2026)
Although anesthesia nurses play a crucial role in managing perianesthetic emergencies, various reports continue to indicate delays and inaccuracies in clinical interventions due to limited clinical experience and suboptimal training methods. This study aimed to determine the effectiveness of perianesthetic emergency scenario-based simulation training on the preparedness and accuracy of anesthesia nurses’ clinical interventions This study employed a quasi-experimental design with a one-group pretest–posttest approach and was conducted at Siti Rahmah Islamic Hospital from January to June 2026. The study population consisted of all anesthesia nurses working in the operating room, and a total sampling technique was used to recruit 12 respondents. Preparedness was assessed using a questionnaire yielding a Cronbach’s alpha coefficient of 0.841, while the accuracy of anesthesia nurses’ interventions was evaluated using an observation checklist. Data were analyzed using univariate statistics and a paired samples t-test for bivariate analysis. The results showed that most respondents were aged 25–35 years (66.7%), male (58.3%), held a Diploma IV degree in Nurse Anesthesiology (66.7%), and had 0–5 years of work experience (75.0%). The mean preparedness score increased from 38.91 ± 8.20 during the pre-test to 44.25 ± 3.69 during the post-test. Similarly, the mean score for intervention accuracy increased from 12.00 ± 1.47 at pre-test to 12.75 ± 1.05 after receiving perianesthetic emergency scenario-based simulation training. Statistical analysis revealed that scenario-based simulation training had a significant effect on improving anesthesia nurses’ preparedness (p = 0.015) and the accuracy of their clinical interventions (p = 0.032). It can be concluded that scenario-based simulation training significantly improves anesthesia nurses’ preparedness and the accuracy of their clinical interventions.